#TITLE_ALTERNATIVE# - ARDIANTI (NIM 10107047); Pembimbing : Dr. Sri Redjeki Pudjaprasetya, IRMA
Ice melting problem with a moving boundary will be examined in this final project. This problem is known as Stefan problem. Stefan problem will be solved as an analitycal and numerical solution. Finite Diference and Finite Volume Method as a numerical solution will be used to solve Stefan problem. Thereby curves for the position of the boundary between ice and water are produced. From these curves the moving boundary problem can be found. When salt is added to the ice will be explained too. It is seen the melting point and melting time decreases when salt is added.